NIRS-BIDS: Brain Imaging Data Structure Extended to Near-Infrared Spectroscopy - Robert Luke; Robert Oostenveld; Helena Cockx; Guiomar Niso; Maureen J Shader; Felipe Orihuela-Espina; Hamish Innes-Brown; Stephen Tucker; David Boas; Meryem A. Yücel; Remi Gau; Taylor Salo; et al. (Scientific Data)
Abstract Functional near-infrared spectroscopy (fNIRS) is an increasingly popular neuroimaging technique that measures cortical hemodynamic activity in a non-invasive and portable fashion. Although the fNIRS community has been successful in disseminating open-source processing tools and a standard file format (SNIRF), reproducible research and sharing of fNIRS data amongst researchers has been hindered by a lack of standards and clarity over how study data should be organized and stored. This problem is not new in neuroimaging, and it became evident years ago with the proliferation of publicly available neuroimaging datasets. To solve this critical issue, the neuroimaging community created the Brain Imaging Data Structure (BIDS) that specifies standards for how datasets should be organized to facilitate sharing and reproducibility of science. Currently, BIDS supports dozens of neuroimaging modalities including MRI, EEG, MEG, PET, and many others. In this paper, we present the extension of BIDS for NIRS data alongside tools that may assist researchers in organizing existing and new data with the goal of promoting public disseminations of fNIRS datasets.